Search engine optimization for dummies - Kent, Peter, 1957- (--For dummies., 2012)
Increase your online ranking with this beginner guide to SEO! Search engine optimization (SEO) is an integral part of getting a site to rank high in the various search engines in order to attract potential customers. With this new edition of a bestseller, you?ll learn the ins and outs and best practices of successful SEO in order to make your website content more search-engine friendly so that it ranks higher among search engines and draws high-volume traffic. Covers search engine basics to help you get started Introduces new coverage on content marketing and reuse, new tracking tools, platfor.